Activity of the EBNA1 promoter associated with lytic replication (Fp) in Epstein-Barr virus associated disorders. Issue 2 (1st April 2001) - Brink, A A T P; Meijer, C J L M; Nicholls, J M; Middeldorp, J M; van den Brule, A J C
Abstract : Background/Aims —In Epstein-Barr virus (EBV) positive cell lines that are stably infected, three different promoters are known to direct the transcription of EBV nuclear antigen 1 (EBNA1). These are located in the BamHI-C, BamHI-Q, and BamHI-F regions of the viral genome (Cp, Qp, and Fp, respectively). Fp is activated upon induction of the viral lytic cycle. The aim of this study was to investigate the activity of Fp in EBV associated diseases. Methods— Using reverse transcriptase polymerase chain reaction, a qualitative analysis of EBNA1 promoter usage in various EBV associated diseases was performed. Results —Fp driven transcription was detected in the context of primary infection and/or lytic replication; at least a portion of the Fp driven transcripts encoded EBNA1. Qp driven EBNA1 transcripts were detected in most samples across the range of disorders tested. Cp driven EBNA1 transcripts were detected in the context of immune suppression and in samples containing EBV positive (non-neoplastic) lymphoid cells. Conclusions —These results confirm the previously proposed "housekeeping" function of the Qp promoter.